Influence of Self-Confidence, Practice Experience, Learning Outcomes Enterpreneur's Practices and Soul Towards Entrepreneurial Capability Cash Design Vocational Students - Tiasari, Wulidah Ning; Tuwoso, Tuwoso Tuwoso; Irianti, Agus Hery Supadmi; Wu, Mingchang (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2025)
This research aims to find out whether there is a significant simultaneous influence of self-confidence, practical experience, practical learning outcomes, entrepreneurial spirit on the entrepreneurial abilities of Fashion Design Vocational School students in Malang City. In this study, the sample of respondents was 134 students using quantitative methods. The analysis technique uses descriptive and inferential with hypothesis testing using partial correlation and multiple regression analysis techniques with classic assumption tests, namely normality test, linearity test, multicollinearity test, autocorrelation test and heteroscedasticity test. The research is quantitative descriptive in nature. The results of the research show the influence of the independent variables, namely the influence of self-confidence (X1) of 0.00, practical experience (X2) of 0.00, practical learning outcomes (X3) of 0.17, and entrepreneurial spirit (X4) of 0. 01 with the dependent variable, namely entrepreneurial ability (Y) of 0.00, both partially and simultaneously, which is indicated by a probability value of 0.05 which is greater than the Sig probability. (0.05 > Sig), Ηα is accepted and Ηο is rejected, meaning it is significant. Based on the results of analysis using multiple linear regression, the influence of self-confidence, internship experience, practical learning outcomes and entrepreneurial spirit on entrepreneurial ability) on entrepreneurial ability is 85.87% so it can be said that self-confidence provides an effective contribution of 86%, experience industrial work contributed 86%, practical learning results contributed 1% and the entrepreneurial spirit contributed 17%.